The basic RNA-binding domain of HIV-2 Tat contributes to preferential trans-activation of a TAR2-containing LTR. - Chang, Y N (1992)
Human immunodeficiency viruses HIV-1 and HIV-2 encode a Tat protein that trans-activates the respective viral genome through RNA targets (TAR1 and TAR2). Tat-1 and Tat-2 have considerable homology. However, an interesting biological observation has been that Tat-1 activates the HIV-1 and HIV-2 LTRs equally while Tat-2 activates the former, in comparison to the latter, poorly. Here, we present evidence that it is the TAR2 RNA target together with the basic RNA-binding protein domain of Tat-2 that dictate this non-reciprocity in trans-activation.